COMPARATIVE STUDY ON EFFICACY OF ERANDA HARITAKI AND ERANDA SHUNTI IN THE MANAGEMENT OF AMAVATA - Deshmukh, *Sourabh Gyanranjan; Ade, Vinod; Thakre, Trupti (International Journal of Ayurveda and Pharma Research, 2018)
Amavata, is a disease described in detail by Madhavakara in Madava Nidana. The word Amavata is made up of Ama and Vata. Aam is produced due to derangement of Jatharagni. This Aam then gets accumulated in Kostha, Sandhi and Trika with vitiated Vata and produce Stabdhata in body, swelling over joints and severe pain in multiple joints this condition is called Aamvata. This clinical feature of Aamvata is markedly similar to Rheumatoid Arthritis, which is a chronic autoimmune disease. Aim- To compare the efficacy of Erandaharitaki & Erandashunti as Abhyantarpana and Matrabasti in Aamvata. Materials & Methods: In the present study 80 patients (40 patients in each group) of Aamvata having aged between 20 to 65 years, fulfilling the inclusion criteria were selected from the OPD and IPD of Kayachikitsa Department of MGACH & RC, Salod (H), Wardha (Maharashtra). All patients were investigated for ESR and RA titre and were treated in two different groups with administration of Erandaharitaki in Group A and Eranda Sunthi in group B was given for Abhyantar Pana and Matrabasti. Results: After the treatment of 30 days, the improvement was observed in the symptoms of both the groups. The result of this treatment showed the improvement was better in Group A Abhyantarpana & Matrabasti with Erandaharitaki tailam in comparison to Group B Abhyantarpana & Matrabasti with Erandashunti tailam. Conclusion: The present study revealed the efficacy of Ayurveda therapy including both Abhyantarpana and Matrabasti for duration of 30 days in the management of Aamvata.